2005
DOI: 10.1002/humu.9378
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variant characterization in intron 4 of the surfactant protein B gene

Abstract: Genetic variants in intron 4 of the surfactant protein B gene SFTPB have been associated with pulmonary morbidity in newborn infants and adults. Genetic variant discovery in intron 4 requires high fidelity polymerase amplification due to a variable number of intermotif dinucleotide repeats and reliable characterization of alleles genetically distinct due to insertion, deletion, or both of 11 conserved sequence motifs. To optimize genetic variant discovery, we selected a high fidelity polymerase enzyme by repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…We did not have sufficient power to pursue the contribution of these more rare mutations to the disease-based risk for RDS in our neonatal intensive care unit cohort that was not enriched for lethal RDS. Common variants in SFTPB and SFTPC with minor allele frequencies Ն0.2 have also been associated with the risk for RDS, but the mechanisms by which these variants and combinations thereof impart risk are undetermined (27)(28)(29)(30). To our knowledge, the contribution of common variants in ABCA3 to the risk of RDS has not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…We did not have sufficient power to pursue the contribution of these more rare mutations to the disease-based risk for RDS in our neonatal intensive care unit cohort that was not enriched for lethal RDS. Common variants in SFTPB and SFTPC with minor allele frequencies Ն0.2 have also been associated with the risk for RDS, but the mechanisms by which these variants and combinations thereof impart risk are undetermined (27)(28)(29)(30). To our knowledge, the contribution of common variants in ABCA3 to the risk of RDS has not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that intronic variant is very important for genetic diseases clinical diagnosis and sometimes as a cause of monogenic disorders and hereditary cancer syndromes [ 9 , 23 ]. Hamvas et al found that Genetic variants in intron 4 of the surfactant protein B gene SFTPB is associate with pulmonary morbidity in newborn infants and adults [ 24 ]. Weisschuh et al assigned pathogenicity to POC1B novel deep Intronic and non-canonical splice site variants [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…We omitted 380 bps in intron 4 due to inability of BigDye terminator sequencing chemistry to resolve multiple CA dinucleotide repeats in this region [26] as well as intron 10, untranslated exon 11, and the 3′ untranslated region.…”
Section: Methodsmentioning
confidence: 99%